Liquid Formulation of AbobotulinumtoxinA Exhibits a Favorable Efficacy and Safety Profile in Moderate to Severe Glabellar Lines: A Randomized, Double-Blind, Placebo- and Active Comparator-Controlled Trial. (14th February 2017) - Ascher, Benjamin; Kestemont, Philippe; Boineau, Dominique; Bodokh, Isaac; Stein, Annette; Heckmann, Marc; Dendorfer, Markus; Pavicic, Tatjana; Volteau, Magali; Tse, Anissa; Picaut, Philippe; Rzany, Berthold
Abstract: Background: In most countries, approved botulinum toxin type A formulations require reconstitution before injection. Objectives: To evaluate the efficacy and safety of a ready-to-use liquid formulation of abobotulinumtoxinA (abobotulinumtoxinA solution for injection, ASI) in subjects with moderate to severe glabellar lines (GL). Methods: In this Phase II, double-blind, placebo-controlled, randomized study, 176 female subjects (aged 30 to 60 years) were randomized into five treatment groups: ASI 20, 50, or 75 U, reconstituted abobotulinumtoxinA (aboBoNT-A) 50 U, and placebo. GL severity was assessed at maximum frown using a 4-point grading scale. Responders were subjects with severity grade of moderate [2] or severe [3] at baseline improving to none [0] or mild [1], evaluated at each time-point by Investigator's Live Assessment (ILA) or Subject's Self-Assessment (SSA). Safety profiles were also determined. Results: Baseline characteristics were similar across groups. Responder rates on Day 29 by ILA were significantly greater for ASI 20, 50, and 75 U versus placebo (88.9%, 91.4%, and 87.9% vs. 0%, respectively; P < 0.0001). Similar results were observed by SSA. A greater proportion of responders was observed in ASI groups vs placebo from Day 8 to 113 for ILA and SSA ( P < 0.001). AboBoNT-A responder rate on Day 29 for ILA was 77.1% ( P < 0.1006 vs ASI 50 U); with comparable results by SSA. The ASI safety profile was comparable to that of aboBoNT-A. Conclusions: Ready-to-use liquid formulation of abobotulinumtoxinA was shown to be efficacious, with comparable results to reconstituted abobotulinumtoxinA, and to have a favorable safety profile in subjects with severe to moderate GL. Level of Evidence: 1: